Evaluation of Herb–Drug Interaction Between Danshen and Rivaroxaban in Rat and Human Liver Microsomes - Wang, Xu; Fa, Jingjing; Zhang, Yuanjin; Huang, Shengbo; Liu, Jie; Gao, Junqing; Xing, Lina; Liu, Zongjun; Wang, Xin (Frontiers in Pharmacology, 2022)
The combination of Salvia miltiorrhiza (Danshen) and rivaroxaban is a promising treatment option in clinical practice in China, but the herb-drug interaction between Danshen and rivaroxaban remains unclear. Therefore, this study aims to reveal the interaction between Danshen and rivaroxaban. We not only investigated the inhibitory properties of Danshen tablet on rivaroxaban metabolism in rat and human liver microsomes, but also evaluated the inhibitory effects of Danshen tablet and its eight active components (dihydrotanshinone I, tanshinone I, tanshinone IIA, cryptotanshinone, danshensu, salvianolic acid A, salvianolic acid B, and salvianolic acid C) on cytochrome P450 (CYP) enzymes. The results showed that Danshen tablet potently inhibited the metabolism of rivaroxaban in rat and human liver microsomes. In the CYP inhibition study, we found that dihydrotanshinone I, the active components of Danshen tablet, potently inhibited the activities of rat CYP3A and CYP2J, with IC50 value at 13.85 and 6.39 μM, respectively. Further inhibition kinetics study, we found that Danshen tablet is a mixed inhibitor in rivaroxaban metabolism in rat and human liver microsomes, with the Ki value at 0.72 and 0.25 mg/mL, respectively. In conclusion, there is a potential interaction between Danshen tablet and rivaroxaban. Danshen tablet inhibits the metabolism of rivaroxaban, which may be because its lipid soluble components such as dihydrotanshinone I strongly inhibit the activities of CYP enzymes, especially CYP3A and CYP2J. Therefore, when Danshen tablet and rivaroxaban are used simultaneously in clinic, it is necessary to strengthen the drug monitoring of rivaroxaban and adjust the dosage.